Examining Operating Efficiency of U.S. Hotels: A Window Data Envelopment Analysis Approach. Issue 7 (3rd October 2017) - Xu, Xun; Chi, Christina Geng-qing
ABSTRACT: Hotels with higher operating efficiency also record better financial performance. Measuring and comparing hotels' operating efficiency provide a benchmarking tool for hoteliers. Using a window data envelopment analysis (DEA) approach, this study examines the operating efficiency of U.S. hotels with various types, geographic locations, sizes, and room rates from a dynamic perspective by analyzing the efficiency stability and trend from year 2007 to year 2014. According to hotels' average trend operating efficiency score and most recent operating efficiency score calculated using PKF Trends data, we categorize hotels into four groups. The categories of hotels having the highest and lowest operating efficiency are identified and compared. Managerial implications of enhancing hotels' operating efficiency are discussed.